Pathways into mental health care for UK veterans: a qualitative study. Issue 1 (1st January 2017) - Mellotte, Harriet; Murphy, Dominic; Rafferty, Laura; Greenberg, Neil
ABSTRACT: Background : It is well established that veterans suffering from mental health difficulties under use mental health services. Objective : This study aimed to understand more about the barriers that prevent veterans from seeking professional help and the enablers that assist veterans in seeking professional help. It also aimed to explore potential mechanisms to improve veterans' help-seeking and pathways to care. Method : The study employed a qualitative design whereby 17 veterans who had recently attended specialist veteran mental health services took part in semi-structured interviews. The resultant data were analysed using grounded theory. Results : Participants described two distinct stages to their help-seeking: initial help-seeking and pathways through treatment. Specific barriers and enablers to help-seeking were identified at each stage. Initial barriers included recognizing that there is a problem, self-stigma and anticipated public stigma. Initial enablers included being in crisis, social support, motivation and the media. Treatment pathway barriers included practical factors and negative beliefs about health services and professionals. Treatment pathway enablers included having a diagnosis, being seen in a veteran-specific service and establishing a good therapeutic relationship. Participants provided some suggestions for interventions to improve veterans' help-seeking in future; these focussed on enhancing both veterans and health professionals' knowledge regarding mental health difficulties. Conclusions : This study identified a number of barriers and enablers that may impact a veteran's journey in seeking help from professional services for mental health difficulties. Enablers such as reaching a crisis point, social support, the media, having a diagnosis of PTSD and veteran-specific mental health services appeared to be important in opposing stigma-related beliefs and in supporting veterans to engage in help-seeking behaviours.